(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Superconducting technology has wide applications in superconducting generator, superconducting transmission lines and superconducting energy storage systems. Most of the studies undertaken conclude that although the application of superconducting material in power system did indeed lead to improved efficiencies, the capital cost and cooling energy requirement were too large and that it was not economically feasible to implement. But the major result in the following studies is that in the future, a full superconducting urban area distribution level power system could be cost-effective with existing solutions. It also offers lower voltage drop and improved stability. The studies employ the use of High-Temperature Superconductors (HTS) cables and HTS current limiters. HTS power equipment has reached such a maturity level that its large-scale integrated use will be feasible in up coming years. Energy savings from efficient power transmission and distribution can align with the decarbonized electric vehicles market.